1971
DOI: 10.1021/jo00800a003
|View full text |Cite
|
Sign up to set email alerts
|

Mesoionic compounds. XIII. 1,4-Dipolar-type cycloaddition reactions of anhydro-2-hydroxy-1-methyl-4-oxopyrido [1,2-a] pyrimidinium hydroxide

Abstract: The title six-membered mesoionic compound (1) undergoes cycloaddition reactions with acetylenic dipolarophiles to yield 1,2-disubstituted 4ff-quinolizin-4-ones (3), with extrusion of methyl isocyanate. With tetracyanoethylene and diethyl azodicarboxylate, no cycloadducts were obtained; rather, substitution occurred at the 3 position of the nucleus. Reaction of 2-jV-methylaminopyridine with carbon suboxide provided an extremely facile synthesis of the mesoionic compound 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It was found that after cleavage of the N-C bond and subsequent formation of the C-C bond (on account of cyclization at the exocyclic carbon atom) these models can and must be transformed into 2-alkylaminopyridines. Thus, 1,4,6-trimethylpyrimidinium iodide (18) is readily hydrolyzed when heated with an aqueous solution of alkali, forming acetylacetone. The action of an aqueous solution of ammonia led to N-demethylation with the formation of 4,6-dimethylpyrimidine (19), while an aqueous solution of methylamine gave a mixture of amines 20 and 21.…”
Section: Rearrangements Of 2-alkylpyrimidinium Saltsmentioning
confidence: 99%
“…It was found that after cleavage of the N-C bond and subsequent formation of the C-C bond (on account of cyclization at the exocyclic carbon atom) these models can and must be transformed into 2-alkylaminopyridines. Thus, 1,4,6-trimethylpyrimidinium iodide (18) is readily hydrolyzed when heated with an aqueous solution of alkali, forming acetylacetone. The action of an aqueous solution of ammonia led to N-demethylation with the formation of 4,6-dimethylpyrimidine (19), while an aqueous solution of methylamine gave a mixture of amines 20 and 21.…”
Section: Rearrangements Of 2-alkylpyrimidinium Saltsmentioning
confidence: 99%
“…The waveguide mode spectrum was obtained by scanning the angle of incidence of the incoming laser beam onto the grating while measuring the out-coupled power with a photo detector situated at the end of the waveguide. [14] From the coupling angles and the known parameter of the grating the effective refractive indices of all modes, N ij , was calculated according to Equation (1). constants of the substrate, the thickness and refractive index for both polarization directions were calculated iteratively as long as at least two modes for each direction could be detected.…”
Section: Synthesis Of Model Compound (4)mentioning
confidence: 99%
“…Mesoionic 6-oxo-1,6-dihydropyrimidin-3-ium-4-olates (1) were first synthesized in 1971 [1,2] and interest in such 6-membered mesoionic heterocycles originally focused on 1,4-dipolar cycloadditions with olefins and alkynes. [3][4][5][6] It was also shown that these compounds are photosensitive and undergo an intramolecular cycloaddition which leads to the formation of bis(b-lactams) (2) [7] as pictured in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoionic 6‐oxo‐1,6‐dihydropyrimidin‐3‐ium‐4‐olates ( 1 ) are six‐membered heterocycles which were synthesized primarily in 1971 1,2. Many experiments were performed in order to investigate 1,4‐dipolar cycloadditions with olefins and alkynes 3–10.…”
Section: Introductionmentioning
confidence: 99%